Using sector-scan sonar for the survey and management of submerged archaeological sites - Henderson, Jon; Abbott, Brian (Wiley, 2017)
This paper reports the results of using a sector scan sonar to record a range of submerged archaeological sites in both shallow and deep water locations. The Kongsberg MS 1000 sector scan sonar was developed for the commercial sector typically to carry out underwater inspections and surveys of bridges, dams, ports and harbours. However, as will be demonstrated below, the ability of the device to rapidly generate high quality, geometrically accurate scans of submerged features, coupled with its relative ease of use and deployment, make it a potentially important new tool for the survey and effective management of underwater archaeological sites.